Premarital health examination legislation : analysis and compilation of state laws (Washington, D.C. : U.S. Department of Health, Education, and Welfare, Public Health Service, Bureau of State Services, Division of Special Health Services, Venereal Disease Program, 1954., 1954)
v, 114 pages ; 24 cm
Includes bibliographical references.